Psychological Assistant: Assessing The Emotional State of a Patient Using Triple Video Analysis Method - ALKAN, MUSTAFA; ELMASRY, WİSAM (Institute of Electrical and Electronics Engineers Inc., 2024)
The 'Psychological Assistant' presents a groundbreaking approach to remote emotion assessment by integrating video analysis techniques, computer vision, speech recognition, and Natural Language Processing (NLP). Leveraging pre-trained models such as Convolutional Neural Networks (CNNs), Support Vector Machines (SVMs), Artificial Neural Networks (ANNs), and advanced NLP algorithms, the system analyzes facial expressions, voice signals, and Text Classification to provide mental health practitioners with comprehensive insights during remote consultations. Through the use of methods such as averaging and combining over time, the system ensures a thorough emotion evaluation, promising high accuracy and reliability in mood identification. This innovative integration of NLP enhances the system's capability to understand and interpret textual cues, allowing for a more holistic assessment of patients' mental states. The technology holds the potential for early intervention, personalized treatment plans, and an elevated standard of care in remote mental health services, representing a significant advancement in digital healthcare solutions. © 2024 IEEE.
8th International Artificial Intelligence and Data Processing Symposium, IDAP 2024
▪️ Date of Conference: 21-22 September 2024.
Keywords: Computer Vision; Facial Expressions; Speech Recognition; Text Classification; Video Analysis